Pelatihan Citizen Report Memanfaatkan Smartphone untuk Mendukung Penyebaran Informasi Melalui Website Desa Borisallo : Pengabdian - Muhammad Zainal Altim; Abdullah Basalamah; Ansarullah; Zulkarnain Hamson; Fadly Kasim (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The implementation of citizen reporting in villages is still hampered by residents' limited knowledge and skills in using digital devices, a lack of understanding of effective news writing, and limited access to information dissemination. This Community Service Program (PKM) activity aims to improve digital literacy, particularly smartphone use, and provide an understanding of the concept, benefits, and practices of citizen journalism. In addition, this activity also trains participants to access and disseminate information through village websites, and motivates them to utilize technology to develop village potential and the village economy. The PKM implementation methods include: (a) needs analysis, (b) designing a training model, (c) implementation using participatory methods, questions and answers, and demonstrations, and (d) evaluation of activity results. The results indicate that this activity is effective in increasing the digital literacy of village officials and the community, as well as strengthening the understanding and practice of citizen journalism. The evaluation also shows a significant increase in the technical and non-technical competencies of participants, as well as a growing awareness and collaborative spirit between village officials and the community in supporting information transparency and digital-based empowerment.